Enhancing biochar steam gasification via frequency-tuned microwave heating for efficient CO2-to-CO conversion - Xinru La; Haolin Liu; Wei Liao; Xi Lin; Bingqing Shi; Yunjuan Sun; Jurong Ren; Lingming Xiong; Shule Wang; Jia Wang; Jianchun Jiang (Biomass and Bioenergy, 2026)

Exogenous raffinose enhances chilling tolerance in postharvest tomato fruit in relation to the scavenging of ROS, maintenance of energy homeostasis, and cell wall integrity - Weimin Ning; Bingqing Qian; Pan Zou; Yukun Shu; Zhiyuan Wang; Qinlu Zheng; Pan Shu; Yun Zhu; Yuan Qing; Zhong Zhang; Lin Shen (Postharvest Biology and Technology, 2026)

Ethylene signaling, pathogenesis-related proteins (PRs) and SlCBF1 collectively regulate Botrytis cinerea resistance in postharvest tomato fruit under low temperature conditions - Pan Shu; Zhiyuan Wang; Bingqing Qian; Zhiyin Yu; Qinlu Zheng; Xin Yao; Hongye Fu; Yuan Qing; Xiaojuan Yin; Pan Zou; Jing Li; Lin Shen (Postharvest Biology and Technology, 2026)

The role of the subcortical structures in subthreshold depression: evidence from static and dynamic functional connectivity - Siying Zhang; Lijun Ma; Jiangzhou Sun; Yujie Chen; Yuanyun He; Qiutong Long; Bingqing Jiao; Huiyuan Huang; Lei Mo; Jiabao Lin (Brain Structure and Function, 2026)

Highly efficient detection of imidacloprid in agricultural samples based on ZIF-8-derived carbon particles-modulated fluorescence polarization immunoassay - Rui Sun; Pei Lv; Bingqing Shen; Qian Wu; Yuan Xue; Lin Chen; Weibin Li; Zhenjiang Liu (Food Chemistry, 2026)

The Dorsal CA2 to Ventral CA1 Circuit Contributes to Spatial and Context-Dependent Memories - Ning Li; Bingqing Zhao; Xiaowen Shen; Hua He; Jianxiang Zhou; Jing Zhang; Lin Xu; Xiaochun Chen; Chun Xu (Neuroscience Bulletin, 2026)

Selective catalytic conversion of polyphenylene oxide waste into benzene and toluene for hydrogen storage via zeolite-controlled hydro-pyrolysis - Bingqing Shi; Dongxian Li; Xi Lin; Shule Wang; Xianzhi Meng; Yanghao Jin; Jia Wang; Jianchun Jiang (Journal of Environmental Chemical Engineering, 2026)

Acidification and deoxygenation matter in assessing redistribution of global cold‐water coral biodiversity induced by climate change - Shuaishuai Liu; Bingqing Xiao; Ákos Bede‐Fazekas; Stefano Mammola; Jorge García Molinos; Jamie M. Kass; Jorge Assis; Chen Lin; Junmei Qu; Hongwei Huang; Qiang Lin; Zhixin Zhang (Limnology and Oceanography, 2026)
The ocean is undergoing significant changes, including warming, acidification, and deoxygenation, which pose great challenges to marine biodiversity. However, most models projecting the impacts of climate change on marine species overlook predictor variables critically meaningful for species' ecologies such as pH and dissolved oxygen. The recent release of high‐resolution projections of different future climate‐change scenarios offers the opportunity to explore species redistribution under multiple threats beyond ocean warming. Accordingly, we conducted a global comparative analysis to study the impact of incorporating predictor variables describing pH and dissolved oxygen into marine species distribution models. We used models trained for 268 cold‐water coral species to project potential future distributions for different climate and dispersal scenarios over different time periods. We found that, irrespective of scenario or period, models using pH and dissolved oxygen projected 11.5–21.4% higher impacts of climate change than those without them. For instance, by the end of the century under a high emission scenario, models including pH and oxygen projected an average range contraction of 48.2% for cold‐water corals under a no‐dispersal scenario, compared with a 26.8% contraction projected by models excluding these two predictors. Given the substantial differences in the predicted distribution patterns and the biological importance of these variables, we highlight that researchers should consider more diverse sets of predictor variables when predicting future range shifts for marine biodiversity assessments under climate change.

Efficient adsorption of U(VI) from seawater on tannin-immobilized conjugated micro-mesoporous poly(aniline)s - Xiaoying Lin; Bingqing Huang; Yifan Liu; Yuancai Lv; Chunxiang Lin; Jianhui Huang; Minghua Liu; Xiaoxia Ye; Jie Chen (Desalination, 2026)

N, S, P co-doped carbon dots with yellow emission for high-sensitivity detection and bioimaging of α-lipomycin in salt-sensitive hypertension - Xianfeng Wang; Liyuan Meng; Dapeng Zhou; Bingqing Zhao; Yuanhang Yu; Fengwu Lin; Mingzhu Gao; Gongle Shen; Yang Luo (Chemical Engineering Journal, 2026)

M2 macrophages alleviate podocyte apoptosis induced by supernatant of glomerular mesangial cells with aIgA1 via targeting UCHL1 - Yuanjie Lin; Bingqing Liu; Zhengjie Wang; Lantao Dai (In Vitro Cellular & Developmental Biology - Animal, 2026)

Joint technique “parallel peptide synthesis & de novo sequencing” development for the structure verification and high-throughput activity screening of biological peptides from sea cucumber (Stichopus japonicus) intestinal hydrolysate - Yimeng Li; Shengfang Gao; Xiaohui Zhang; Zhuo Cao; Youyou Guo; Runkun Zhao; Yonggang Liu; Xinxin Li; Hongying Lin; Qi Qin; Bingqing Yi; Guodong Zhao (Food Research International, 2025)

Real and long-time predicting the trajectories of internal solitary waves: Case studies in the Sulu Sea - Longyu Huang; Jingsong Yang; Lin Ren; Zetai Ma; Yu Chai; Peng Chen; Shuangyan He; Bingqing Liu; Antony K. Liu (Ocean Engineering, 2025)

Biocompatible and stretchable chitosan piezoelectric gel with antibacterial capability and motion monitoring function for Achilles tendon rupture treatment - Zhencheng Xiong; Bingqing Lin; Cheng Huang; Ao Duan; Chaoyi Zhang; Guangliang Qiang; Wenzheng Liu; Renliang Zhao; Xiangtian Deng; Dong Wang; Zilu Ge; Guanglin Wang; et al. (Carbohydrate Polymers, 2025)

A systematic evaluation of population pharmacokinetic models for polymyxin B in patients with liver and/or kidney dysfunction - Xueyong Li; Yu Cheng; Bingqing Zhang; Bo Chen; Yiying Chen; Yingbing Huang; Hailing Lin; Lili Zhou; Hui Zhang; Maobai Liu; Wancai Que; Hongqiang Qiu (Journal of Pharmacokinetics and Pharmacodynamics, 2024)

Effects of Fe(III) on the formation and toxicity alteration of halonitromethanes, dichloroacetonitrile, and dichloroacetamide from polyethyleneimine during UV/chlorine disinfection - Tingting Huang; Lin Deng; Shui Wang; Chaoqun Tan; Jun Hu; Bingqing Zhu; Mengya Li; Lianghua Lu; Zhihua Yin; Bowen Fu (Water Research, 2024)

Generation of diurnal internal solitary waves (ISW-D) in the Sulu Sea: From geostationary orbit satellites and numerical simulations - Longyu Huang; Jingsong Yang; Zetai Ma; Bingqing Liu; Lin Ren; Antony K. Liu; Peng Chen (Progress in Oceanography, 2024)

PASS4SWAT: Orchestration of containerized SWAT for facilitating computational reproducibility of model calibration and uncertainty analysis - Qiaoying Lin; Dejian Zhang; Jiefeng Wu; Xingwei Chen; Yihui Fang; Bingqing Lin (Environmental Modelling & Software, 2024)

Different responses of event-based flood to typhoon and non-typhoon rainstorms under land use change in Xixi Basin of southeastern China - Hong Cheng; Bingqing Lin; Siran Ying; Xingwei Chen; Qingyong Chen; Huaxia Yao (CATENA, 2024)

Building a predictive model for hypertension related to environmental chemicals using machine learning - Shanshan Liu; Lin Lu; Fei Wang; Bingqing Han; Lei Ou; Xiangyang Gao; Yi Luo; Wenjing Huo; Qiang Zeng (Environmental Science and Pollution Research, 2023)

HMS-REST v1.0: A plugin for the HEC-HMS model to provide RESTful services - Qiaoying Lin; Bingqing Lin; Dejian Zhang; Jiefeng Wu; Xingwei Chen (Environmental Modelling & Software, 2023)

Dual photoelectrodes activate oxygen evolution and oxygen reduction reactions enabling a high-performance Zn-air battery and an efficient solar energy storage - Jia You; Bingqing Zhang; Xianlong Wang; Haoran Zhang; Lanlan Huang; Lihua He; Nanxin Li; Yichen Chang; Shiwei Lin (Chemical Engineering Journal, 2023)

An efficient model to estimate the soil profile and stratigraphic uncertainty quantification - Lin-Shuang Zhao; Shuaihe Zhuo; Bingqing Shen (Engineering Geology, 2023)

Origin traceability of bottled mineral water imported into China using chemical and stable isotope fingerprints - Hao Wu; Haiquan Chen; Bingqing Yi; Karyne M. Rogers; Xuehai Bian; Ni Lin; Xiuwen Zhou; Baohui Jin; Zhi Yan; Haichao Zhou (Journal of Hydrology, 2023)